A new expandable non‐isolated opposite polarity boost DC–DC converter with fewer switches. Issue 15 (9th June 2022) - Mohammadzadeh Shahir, Farzad; Babaei, Ebrahim; Sabahi, Mehran
Abstract: Here, a new structure is proposed for non‐isolated opposite polarity boost DC–DC converter with expandability into a n‐cell converter using D‐D‐D‐C‐L cell. In comparison with conventional non‐isolated boost converters, the main provided advantages by the proposed converter are lower currents stress of switching, modular structure and high voltage gain with two degrees' freedom due to cell number and duty cycle. The modular structure of the proposed converter is designed without adding any switch for higher cells whereas decreasing inductances values. Here, the relation between voltage and current of all elements in continuous conduction mode (CCM) and discontinuous conduction mode (DCM) is calculated as well as voltage gain in each mode. Also, the current stress of switches and critical inductance are obtained. Then, the performance of proposed converter is compared with other solutions in term of voltage gain in CCM, the number of elements and switches. In addition, the voltage gain in CCM and DCM, and critical inductance relations are extracted. By increasing the number of cells in the proposed converter, high voltage gain is obtained at low duty cycle. Finally, operating of the proposed converter is examined using experimental and PSCAD/EMTDC to analysis of theoretical concepts.